Текст-типологічні особливості соціально-політичного есе в американській лінгвокультурній традиції: хронотопний контекст - Торговець, Юлія Іванівна; Torhovets, Yu. I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто хронотопний контекст текстового рівня СПЕ американської лінгвокультурної традиції початку ХХІ ст. Проаналізовано інваріантні та варіативні текст-типологічні ознаки хронотопного контексту СПЕ у різних позиціях тексту. У межах хронотопного контексту дослідженню підлягає текстова категорія об’єктивної модальності. Ономастичні одиниці (антропоніми, топоніми) і реалії розглядаємо як безпосередні експлікатори категорії часу та простору. The article focuses on chronotopic context of textual level of socio-political essay in American lingua-cultural tradition. Variable and invariable text-typological features of SPE in chronptopic context have been analyzed in this research. Functioning of real objective modality, which is implemented through the use of Present Simple / Perfect / Continuous and Past Simple, is regarded as invariable feature of chronotopic context of SPE in initial position of the text. Medial position of SPE is characterized by the use of, along with real objective modality, unreal objective modality of possibility, desirability and necessity. Functioning of unreal modality can be regarded as invariable text-typological features of SPE in final position of the text. Analysis shows that chronotopic markers, such as anthroponyms, toponyms and realities, explicate textual categories of time and space.
Text Typological Features of Socio-Political Essay in American Lingua-Cultural Tradition: Chronotopic Context
Keywords: об’єктивна модальність; objective modality; хронотопні маркери; chronotopic markers; інваріантні / варіативні текст-типологічні ознаки; invariable/variable text-typological features